Supervision, Sanctions, and Leadership as Determining Factors of Employee Work Discipline at the Department of Transportation of Binjai City - Muhammad Diva Alfiazli; Sri Rahayu (Lembaga Riset dan Inovasi Al-Matani, 2025)
This research was conducted at the Department of Transportation of Binjai City with the aim of examining the influence of work supervision, punitive sanctions, and leadership on employee work discipline in performing their duties. The population consists of 75 permanent employees, and the sampling technique used was a saturated sample, resulting in a total of 75 respondents. The type of data used is primary data, with secondary data serving as the data source. Data collection techniques included literature studies, surveys, and observations. The data analysis techniques used were multiple linear regression, classical assumption tests, and hypothesis testing. The results of the study show that work supervision, punitive sanctions, and leadership have a positive and significant influence—both partially and simultaneously—on employee work discipline at the Department of Transportation of Binjai City. There is a moderate correlation between work supervision, punitive sanctions, and leadership with employee discipline. Employee work discipline can be explained by work supervision, punitive sanctions, and leadership by 43.5%, while the remaining 56.5% can be explained by other variables not examined in this study.